Adipose‐Derived Regenerative Cell Transplantation for the Treatment of Hand Dysfunction in Systemic Sclerosis: A Randomized Clinical Trial. Issue 8 (27th June 2022) - Khanna, Dinesh; Caldron, Paul; Martin, Richard W.; Kafaja, Suzanne; Spiera, Robert; Shahouri, Shadi; Shah, Ankoor; Hsu, Vivien; Ervin, John; Simms, Robert; Domsic, Robyn T.; Steen, Virginia; et al.
Abstract : Objective: Hand dysfunction is common in systemic sclerosis (SSc). We undertook this study to evaluate the capacity of autologous adipose‐derived regenerative cells (ADRCs) to improve hand function in SSc patients. Methods: The Scleroderma Treatment with Celution Processed Adipose Derived Regenerative Cells Trial was a prospective, randomized, double‐blind trial of ADRCs, in which ADRCs were obtained from patients with SSc by small‐volume adipose tissue harvest, and the fingers of each patient were injected with ADRCs. The primary end point was change in hand function at 24 and 48 weeks, assessed using the Cochin Hand Function Scale (CHFS). One of the secondary end points included the change in Health Assessment Questionnaire disability index (HAQ DI) at 48 weeks. Separate prespecified analyses were performed for patients with diffuse cutaneous SSc (dcSSc) and those with limited cutaneous SSc (lcSSc). Results: Eighty‐eight patients were randomized to receive ADRCs (n = 48 [32 patients with dcSSc and 16 with lcSSc]) or placebo (n = 40 [19 patients with dcSSc and 21 with lcSSc]). Change in hand function according to CHFS score was numerically higher for the ADRC group compared to the placebo group but did not achieve statistical significance (mean ± SD improvement in the CHFS score at 48 weeks 11.0 ± 12.5 versus 8.9 ± 10.5; P  = 0.299). For patients with dcSSc, the between‐group difference in the CHFS at 48 weeks was 6.3 points (nominal P  = 0.069). For the secondary end point, the dcSSc group exhibited a between‐group difference of 0.17 points in the HAQ DI (nominal P  = 0.044) at 48 weeks. Of the ADRC‐treated patients with dcSSc, 52% reported improvement greater than the minimum clinically important difference for both CHFS and HAQ DI compared to 16% in the placebo group (nominal P  = 0.016). Small‐volume adipose tissue harvest and ADRC treatment were well tolerated. Conclusion: While the primary end point of this trial was not achieved, efficacy trends were observed in patients with dcSSc. Adipose tissue harvest and ADRC injection were demonstrated to be feasible. Further clinical trials of this intervention in the setting of dcSSc are warranted.